Transforming Capitalism through Real Utopias - Wright, Erik Olin (American Sociological Review, 2013)
This address explores a broad framework for thinking sociologically about emancipatory alternatives to dominant institutions and social structures, especially capitalism. The framework is grounded in two foundational propositions: (1) Many forms of human suffering and many deficits in human flourishing are the result of existing institutions and social structures. (2) Transforming existing institutions and social structures in the right way has the potential to substantially reduce human suffering and expand the possibilities for human flourishing. An emancipatory social science responding to these propositions faces four broad tasks: specifying the moral principles for judging social institutions; using these moral principles as the standards for diagnosis and critique of existing institutions; developing an account of viable alternatives in response to the critique; and proposing a theory of transformation for realizing those alternatives. The idea of “real utopias” is one way of thinking about alternatives and transformation.